Recuperação de sais de efluentes de cultivo de microalgas por osmose inversa para reúso in loco - Soster, Aline Manfroi (2018)
The cultive of microalgae has growing and has been the focus of innumerable biotechnological research. The production of Spirulina platensis in a synthetic environment require of control of several factors, as well as addition of nutrients and water. In order to reduce production costs and treatment of microalgae wastewater, the membrane separation process of reverse osmosis can be very effective in salt retention and in the production of permeates that enable reuse. This study investigated the reverse osmosis as an alternative for sustainability in cultivation of microalgae, by evaluating their potential in the treatment and salts residual water retention for later reuse of the retained and permeated. Was collected 120 L of Spirulina platensis effluent and treated by reverse osmosis, obtaining, later, samples of effluent retained (concentrate) and permeated (treated) for concentration factors 1, 2, 3 and 4. Thus, was made the characterization of the samples: raw, concentrated and treated for performed new crops. The medium cultivation were prepared in a discontinuous mode for the obtaining biomass and characterization of the same. The results demonstrate that the reverse osmosis is promising and innovative to treat the residual water of Spirulina platensis. The membrane reached a permeate flow of 26.5 L.m².h-1at bar of pressure 25 ºC of temperature. For the components: Iron, Magnesium, Sodium, Potassium, Ammoniacal Nitrogen, Phosphorus, Carbonates, color and turbidity the rejection efficiency reached 100%. Clacium, Organic Matter, Nitrates, Sulphates, Chlorides, Total Nitrogen, Total Suspended Solids, Alkalinity, Conductivity showed results between 91% and 99,4%. The physical parameters of: Color and Turbidity the rejection generated results between 99.3 % and 100 %. The growth kinetics of the Spirulina platensis biomass proves that the retained and permeated can be used as a new culture medium. The carbohydrate concentration of the reused medium reached 59.28 % and 25.5 mg.L-1.d-1, demonstrating that this new medium can be used to produce microalgae biomass.